Determining Critical Soil pH for Sunflower Production - Apurba Sutradhar; Romulo P. Lollato; Katy Butchee; Daryl B. Arnall (International Journal of Agronomy)
Soil acidity has become a major yield-limiting factor in cropping systems of the Southern Great Plains, in which winter wheat (Triticum aestivum L.) is the predominant crop. Sunflower (Helianthus annuus L.) is a strong rotational crop with winter wheat due to its draught and heat tolerance. However, the effects of low soil pH on sunflower productivity have not been explored. The objective of this study was to determine the critical soil pH and aluminum concentration (AlKCl) for sunflower. Sunflower was grown in a randomized complete block design with three replications of a pH gradient ranging from 4.0 to 7.0 at three locations with varying soil types. Soil pH was altered using aluminum sulfate (Al2(SO4)3) and hydrated lime (Ca(OH)2). Plant height, vigor, and survivability were all negatively affected by soil acidity. Sunflower yield was reduced by 10% at or below soil pH 4.7 to 5.3 dependent upon location and soil type. Levels of AlKCl above 6.35 mg kg−1 reduced seed yield by 10% or greater. We concluded that sunflower may serve as a better rotational crop with winter wheat under acidic conditions when compared to other adaptable crops.